Tuberculoma of Central Nervous System with Right Sided Hemiparesis - Iqbal, Shahed; Akter, Wahida; Badruddoza, M; Chowdhury, Mahmood Ahmed (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Tuberculoma is one of the manifestations of Central Nervous System (CNS) tuberculosis (TB). A tuberculoma is a tuberculous focus, which enlarges with in brain tissue, firm, avascular, spherical masses, with size varying between 2 cm to 10 cm in diameter and the compressed surrounding tissue shows edema and gliosis. Tuberculoma resuls from aggregation of caseous tubercle that usually manifest clinically as brain tumour. Tuberculomas account for upto 40% of brain tumours in some areas of the world. In adults tuberculomas are most often supratentorial, but in children they are often infratentorial, located at the base of the brain near the cerebellum. Lesions are most often singular but may be multiple. The most common symptoms are headache, fever & convulsion & also may give rise to signs of raised intracranial pressure or a hemiplegia, or cranial nerve palsy if in the brain stem. Here described a case of 4 years old female child who presented with the complants of high grade fever for 10 days duration followed by right sided weakness for 4 months. She had 6,sup>th and 7th cranial nerve palsy with exaggerated reflex on right side. Her tuberculin test was positive but Cerebro Spinal Fluid (CSF) study was normal & Magnetic Resonance Imaging (MRI) of brain showed rim enhancing lesion. Early recognition and timely treatment of CNS TB is critical if the considerable mortality and morbidity associated with the condition is to be prevented. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22892 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 74-76